The Influence of Continuous Multi Stage Countercurrent Extraction Process (CMCE) Propolis Extract Administration on Superoxide Dismutase Activity and Hepatocytes Fibrosis Degree (An Experimental Study on Male Wistar Rats Induced with Carbon Tetrachloride (CCl4)) - Wani, Elsayanti; Nasihun, Taufiqurrachman; Hussaana, Atina (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2020)
Introduction: Continuous Multi Stage Countercurrent Extraction Process (CMCE) propolis extract containing Caffeic Acid Phenethyl Ester (CAPE) may inhibit the formation of lipid peroxidation. However, it is still unclear whether or not CMCE propolis is able to increase SOD activity and reduce acute hepatocytes damages induced by CCl4. Objective: To evaluate the influence of CMCE propolis extract administration in increasing the SOD activity and reducing the hepatocytes fibrosis of male Wistar rats induced with CCl4.Method: an experimental research with a post-test only control group design. Twenty eight male Wistar rats were divided into four groups. Group C-N was only induced with CCl4, while group CM-3, CM-7, and CM-14 were induced with CCl4 and received CMCE propolis extract respectively with 3.6 mg/200 g BW, 7.2 mg/200 g BW, and 14.4 mg/200 g BW. CMCE propolis was administered for 14 days and then CCl4 was administered on the last day. SOD activity was measured using the colorimetric method, while the hepatocytes fibrosis degree was assessed using Image J Software method with NASH score modification.Results: Post Hoc LSD analysis indicated that SOD activity in group CM-3 (51.67 ± 4.20), CM-7 (70.21 ± 6.26), CM-14 (80.85 ± 4.59) was lower than that in group C-N (23.70 ± 5.12) with P <0.05. Meanwhile, the Mann-Whitney U test showed that the hepatocytes fibrosis degree in group CM-3 (0.85 ± 0.69), CM-7 (1.14 ± 0.37), and CM-14 (0.71 ± 0.48) was significantly lower than that in group C-N (2.28 ± 1.25) with p<0.05.Conclusion: The CMCE propolis extract administration was able to increase the SOD activity and reduce the hepatocytes fibrosis degree of male Wistar rats induced with CCl4